OUTCOMES IN PATIENTS WITH BRAIN TRAUMA ASSOCIATED WITH EXTRACRANIAL INJURIES ON IN-HOSPITAL STAGE OF MEDICAL CARE - Yu. V. Puras; A. E. Talypov; V. V. Krylov (Неотложная медицинская помощь, 2016)
INTRODUCTION. The development of prognostic criteria in brain trauma associated with extracranial injuries is necessary for treatment results definition, getting of priority rating, establishment time and volume of care, for active management of clinical process and timely complications warning.PURPOSE. To determine outcomes and predictive value of risk factors in patients with brain trauma associated with extracranial injuries in-hospital stage of medical care.MATERIAL AND METHODS. Retrospective analysis was performed in 1634 patients who were underwent surgery due to severe traumatic brain injury (TBI). There were 22,1% patients with brain trauma associated with extracranial injuries. Using statistical analysis we determined relationships between outcomes and clinical and instrumental signs, obtained during the examination of patients.RESULTS. The extracranial risk factors in patients with brain trauma associated with extracranial injuries were: ISS 40 and over, multiple extracranial injuries, spinal or abdominal injury, age 70 and over, arterial hypoxemia and hypotension, complications in postoperative period. The intracranial risk factors were: GCS score 12 and less, oculomotor nerve dysfunction, abnormal pupil reactivity, pathological motor responses or diffuse muscular tone reducing, brain herniation at the stage of midbrain or pons clinically, brain lesions volume over 90 cm3 , lateral dislocation over 10 mm, absence of basal cisterns on CT scan, VCC-2 less than 8%, brain expansion during surgery.CONCLUSION. Prognostic criteria identified by statistical analysis can be used to assess outcome prognosis at the early stages of medical care in patients with brain trauma associated with extracranial injuries.